Seroprevalence and SARS-CoV-2 antibodies distribution in Portugal following mass vaccination campaign: Irina Kislaya. (25th October 2022) - Kislaya, I; Gonçalves, P; Gaio, V; Matos, R; Barreto, M; Melo, A; Guiomar, R; Rodrigues, A P; ISNCOVID-19 group, PT
Abstract: Introduction: Information on post-infection and vaccine-induced SARS-CoV-2 seroprevalence is important for public health policies. A 3rd wave of National Serological Survey (ISN3COVID-19) was conducted to measure SARS-CoV-2 seroprevalence and characterize specific antibodies distribution in Portuguese population in September - November 2021, following a mass vaccination campaign. Methods: ISN3COVID-19 was a cross-sectional epidemiological study that collected serum samples and questionnaire data on a sample of Portuguese residents aged 1 year or older (n = 4545). SARS-CoV-2 IgG anti-nucleoprotein and anti-spike antibody levels were measured using Abbott Chemiluminescent Microparticle Immunoassays. Seroprevalence was estimated for the overall sample and stratified by age group, sex, region and self-reported chronic conditions. Medians and respective 95% confidence intervals (95%CI) were used to describe the distribution of SARS-CoV-2 antibodies in specific population subgroups. Results: The overall seroprevalence of SARS-CoV-2 (post-infection or vaccine-induced) was 86.4% (95%CI: 85.2 to 87.6%), post-infection seroprevalence was 7.5% (95%CI: 6.6 to 8.5). Higher seroprevalence was observed among 50-59 years-old (96.5%), women (88.3%), and those with two or more self-reported chronic conditions (90.8%). Higher IgG (anti-Spike) levels were estimated for individuals vaccinated with the booster dose (median=12601.3 AU/ml; 95%CI: 4127.5 to 19089.1) and for those vaccinated with two doses of Spikevax® vaccine (median=7012.7 AU/ml, 95%CI: 5568.8 to 8456.6). Conclusions: The SARS-CoV-2 seroprevalence was high and consistent with vaccine coverage in Portugal. Seropositivity was associated with sex, age and previous chronic conditions. The anti-SARS-CoV-2 anti-spike IgG levels varied according to vaccine brand and number of doses. These results show that monitoring seroprevalence and SARS-CoV-2 antibody distribution is of paramount importance to guide public health policies. Key messages: Significant increase in SARS-CoV-2 seroprevalence following the mass vaccination campaign consistent with the high vaccine coverage achieved in Portugal. Continuous monitoring of the population‐level IgG response after vaccination remains important to guide further public health measures.